Contraceptive challenges and the transgender individual - A. Francis; S. Jasani; G. Bachmann (BMC, 2018)
Abstract In recent years public awareness of healthcare disparities experienced by transgender individuals throughout the world have garnered increasing attention within the media and from health advocates. Despite this increasing awareness, a paucity of research data and clinical protocols of care for clinicians continues to exist, especially in regard to the transgender individual's family planning needs. Clinicians should be on the forefront of promoting strategies that forge a meaningful and collaborative relationship with the transgender man, including as he transitions through to the menopause and his sexual and reproductive healthcare needs. Unfortunately, despite best efforts to address the health concerns of transgender men in midlife, including their contraceptive needs and pregnancy desires, there is currently a paucity of research. Although hormonal contraceptives are not an option for this group of individuals, especially those on masculinizing hormones, IUD's, both copper containing and progestin containing, should be considered for those with intact pelvic organs. For this group of transgender men with potential for pregnancy who have either completed their family or choose not to give birth, sterilization can be offered. Regardless of where they identify along the gender spectrum, these midlife individuals with potential reproductive potential should have equitable access to and up to date counseling on their contraceptive options. This commentary addresses the contraceptive challenges of the midlife transgender man. (Note: Pronouns used in this article are he/him for cis and transgender men and she/her for cis and transgender women).